2004
DOI: 10.1080/01650250344000514
|View full text |Cite
|
Sign up to set email alerts
|

Personality and gender differences in friendship needs and experiences in preadolescence and young adulthood

Abstract: Personality and gender differences in close same-sex friendship needs and experiences were investigated in two samples. Participants were 312 university students (217 women, M age 1/4 19.5) and 491 preadolescents (269 girls, M age 1/4 11.87). Participants completed several questionnaires yielding scores for communion and agency (personality), communal and agentic friendship needs, actual communal and agentic provisions of a best friendship, and affective functioning (satisfaction with the best friendship, lone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
45
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 59 publications
6
45
0
6
Order By: Relevance
“…Zarbatany et al (2004) distinguish between two groups of friendship aims or needs, that is, communal needs (i.e., needs for interpersonal closeness, such as intimacy and acceptance) and agentic needs (i.e., needs for individuation, such as network access and admiration). They found that twelve-year-old girls expressed higher communal friendship need than boys, whereas boys expressed higher agentic need.…”
Section: Gender Friendship Aim and Selection Patternsmentioning
confidence: 99%
“…Zarbatany et al (2004) distinguish between two groups of friendship aims or needs, that is, communal needs (i.e., needs for interpersonal closeness, such as intimacy and acceptance) and agentic needs (i.e., needs for individuation, such as network access and admiration). They found that twelve-year-old girls expressed higher communal friendship need than boys, whereas boys expressed higher agentic need.…”
Section: Gender Friendship Aim and Selection Patternsmentioning
confidence: 99%
“…For example Zarbatany et al's (2004) agency-communion theory explains two types of friendship: communal and agentic. In the former, power is distributed equally for the most part, and the friendship itself is measured in terms of interpersonal closeness, which includes a large number of factors such companionship, intimacy, loyalty, security, emotional support, love and affection, nurturance, and mutual past experiences.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Ook stelt men in de literatuur dat zij qua vriendschapbehoeften van elkaar verschillen (Zarbatany, Conley, & Pepper, 2004). Meisjes hebben meer behoefte aan emotionele verbondenheid en vertrouwen, en vriendschappen tussen meisjes zijn exclusiever en emotioneel diepgaander dan die van jongens.…”
unclassified
“…Jongens daarentegen vinden het samen ondernemen van dingen belangrijk in hun vriendschappen. Zij zoeken kameraadschap, plezier en stimulatie bij hun vrienden en hechten in vergelijking met meisjes minder belang aan intimiteit (Zarbatany, Conley, & Pepper, 2002). Buhrmester (1996) concludeert dat meisjes voornamelijk zogenoemde communal needs hebben en jongens vooral agentic needs.…”
unclassified